(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The use of social media has grown significantly in the last few years. Social media refers to "the websites and online tools that facilitate interactions between users by providing them opportunities to share information, opinions, and interest" (Swar and Hameed, 2017, p. 141). Adolescents have been found to be more vulnerable to addiction and crimes related to social media. Hence, the study has tried to understand the association of social media with the well being of adolescents. The first part of the paper deals with the role and relevance of social media.Further, the literature review depicts a strong connection between social media and individuals' well-being. For the quantitative analysis, various statistical techniques are used. In order to evaluate the association between variables, the composite index has been prepared. Further, the ranking has been given to reflect social media's impact on adolescents' well-being. Lastly, a few recommendations have been made for the state government regarding the well being of the adolescents.